Report on the 14th Conference of the Groupe des Cartothécaires de LIBER, 31st August to 4th September, Cambridge, United Kingdom - Jones, Pete (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
The 14th conference of the LIBER Groupe des Cartothécaires was held in Cambridge in what proved to be warm and sunny conditions, very unusual for a late English summer. The conference was excellently organised by the Cambridge University Map Librarian, Anne Taylor, and her backroom team. It built on previous years’ strengths and followed tried and tested patterns. The programme was very varied with speakers from a wide range of countries delivering presentations on developments within their own areas or specialisation. The 2004 Conference theme “Map Collections and GIS or Digital Data - the death of the paper Map?” in some parts echoed the 2002 conference that had started to look at the impact that digital data and archives were beginning to make on collections across the continent. The title was intentionally partially controversial in questioning the death of the paper map, although the subsequent discussions did identify that whilst digital data is certainly all pervasive in the library arena, the demands for traditional paper mapping continue unabated. One of the major themes that came out of many of the presentations was a desire to better understand the scope and complexity of digital data and also the desire to share experiences wherever possible to ensure that the collections were not all going in different directions. There was also a strong desire to burden-share wherever possible, primarily to avoid the duplication of effort where the same material was under consideration for digitisation either as a means of improving access or as a means of preservation.